Associations between Psychological Distress and Body Mass Index among Law Enforcement Officers: The National Health Interview Survey 2004-2010 - Ja K. Gu; Luenda E. Charles; Cecil M. Burchfiel; Michael E. Andrew; Claudia Ma; Ki Moon Bang; John M. Violanti (Safety and Health at Work, 2013)
Objectives: To investigate the association between psychological distress and obesity among law enforcement officers (LEOs) in the United States. Methods: Self-reported data on psychological distress based on six key questions were obtained from LEOs who participated in the National Health Interview Survey (2004-2010). We used Prochaska's cut-point of a Kessler 6 score ≥ 5 for moderate/high mental distress in our analysis. Mean levels of body mass index (BMI) were compared across three levels of psychological distress. Results: The average age of LEOs (n = 929) was 39.3 years; 25% were female. Overall, 8.1% of LEOs had moderate or high psychological distress; 37.5% were obese (BMI ≥ 30). Mean BMI increased with increasing psychological distress (no distress, BMI = 27.2 kg/m2; mild distress, 27.6 kg/m2; and moderate/high distress, 33.1 kg/m2; p = 0.016) after adjustment for age, race, income, and education level among female officers only. Physical activity modified the association between psychological distress and BMI but only among male LEOs (interaction p = 0.002). Among male LEOs reporting low physical activity, psychological distress was positively associated with BMI (30.3 kg/m2 for no distress, 30.7 for mild distress, 31.8 for moderate/high distress; p = 0.179) after adjustment, but not significantly. This association was not significant among males reporting high physical activity. Conclusion: Mean BMI significantly increased as psychological distress increased among female LEOs. A longitudinal study design may reveal the directionality of this association as well as the potential role that physical activity might play in this association.